Butch/Femme differences in substance use and abuse among young lesbian and bisexual women: Examination and potential explanations. - Rosario, Margaret; Schrimshaw, Eric W; Hunter, Joyce (Substance use & misuse, 2008)
The current study examined the role of gender atypical self-presentation on the alcohol, tobacco, and marijuana use, as well as symptoms of substance abuse/misuse, of an ethnically diverse sample of 76 young (ages 14-21 years) lesbian and bisexual women who were interviewed between 1993 and 1995 in New York City. Even after controlling for age, sexual identity, and social desirability, young butch women reported drinking alcohol more frequently and in greater quantity, smoking more cigarettes, and using marijuana more frequently than young femme women. Experiences of gay-related stressful events, internalized homophobia, and emotional distress were found to largely account for the butch/femme differences in tobacco and marijuana use, but not in higher levels of alcohol use. Despite the small convenience sample, these findings suggest that intervention efforts to address the higher levels of substance use among young lesbian and bisexual women may increase effectiveness by also addressing experiences of gay-related stress and emotional distress of young butch women. The study's limitations are noted
Keywords: 1900-1999; 1990-1999; amériques; identités LGBTQIA2+; personnes bisexuelles; personnes lesbiennes; périodes historiques; ressource en ligne; régions géographiques; santé; thématiques; états-unis

The coming-out process of young lesbian and bisexual women: Are there butch/femme differences in sexual identity development? - Rosario, Margaret; Schrimshaw, Eric W; Hunter, Joyce; Levy-Warren, Anna (Archives of sexual behavior, 2009)
Research on lesbian and bisexual women has documented various biological and behavioral differences between butch and femme women. However, little research has examined whether differences exist in sexual identity development (i.e., the coming-out process). The present study examined longitudinally potential butch/femme differences in sexual identity formation and integration among an ethnically diverse sample of 76 self-identified lesbian and bisexual young women (ages 14–21 years). A composite measure of butch/femme identity classified 43% as butch and 51% as femme. Initial comparisons found butch/femme differences in sexual identity (i.e., nearly all butches identified as lesbian, but about half of femmes identified as bisexual), suggesting the need to examine this confound. Comparisons of lesbian butches, lesbian femmes, and bisexual femmes found that lesbian butches and femmes generally did not differ on sexual identity formation, but they differed from bisexual femmes. Lesbian butches and femmes had sexual behaviors and a cognitive sexual orientation that were more centered on women than those of bisexual femmes. With respect to sexual identity integration, lesbian butches were involved in more gay social activities, were more comfortable with others knowing about their homosexuality, and were more certain, comfortable, and accepting of their sexual identity than were bisexual femmes. Fewer differences were found between lesbian femmes and bisexual femmes or between lesbian butches and lesbian femmes. The findings suggest that sexual identity formation does not differ between butch or femme women, but differences are linked to sexual identity as lesbian or bisexual. Further, the findings that lesbian femmes sometimes differed from lesbian butches and at other times from bisexual femmes on sexual identity integration suggest that neither sexual identity nor butch/femme alone may explain sexual identity integration. Research examining the intersection between sexual identity and butch/ femme is needed.
Number: 1
Keywords: butch/femme; discipline; identité sexuelle; identités LGBTQIA2+; personnes bisexuelles; personnes lesbiennes; ressource en ligne; sciences humaines; sexologie; sexualité; thématiques